Opportunities and econometrics for rice (Oryza sativa) fallow pulses in north coastal Andhra Pradesh - SRINIVAS, T; SRIDHAR, T V; BABU, G PRASAD; NAIDU, D CHINNAMA; CHENDRAYUDU, E; RAMBABU, P (The Indian Journal of Agricultural Sciences, 2022)
The present study was carried out during 2022 at the Biotech KISAN Hub unit, Krishi Vigyan Kendra, Banavasi. Constraints in production of fallow pulse crop along with the strategies to overcome them were discussed and addressed in north coastal districts (Srikakulam and Visakhapatnam), which have increased the pulse production and at the same time improved the net returns of the farmers. Majority of the farmers in these districts are small farmers (>85%) and low to medium in their knowledge and adoption levels on sustainable agricultural practices. This project also enhanced the knowledge levels of the farmers pertaining to the benefit and importance of rice fallow pulse cropping and the farmers are ready to adapt this cropping pattern. Rice fallow pulse cropping not only improves the socio-economic status of farmers but also plays a key role in meeting the high demands of pulses and overcoming the malnutrition which is need of the hour. Hence, the remaining rice area as mentioned above 72% under kharif in these districts if utilized for growing pulses in winter (rabi) season which is around 3.11 lakh ha, it can lead to increased pulse production of around 420.2 Mt and can generate an additional income of approximately `2941 crores at low input costs.